APPENDIX III: THE SUBSEQUENT CAREER OF MICHEL DE SEURE. (8th September 2014) - Unknown
Abstract : On returning to France, de Seure was immediately swept into the service of the queen mother at a time of the most intense political and religious crisis so far. In the course of 1562, he became a member of the conseil privé . On 14 April 1562, we find him introducing Throckmorton for an audience with Catherine and then, early in May, he was visiting Throckmorton to announce to him that Paul de Foix had sent word of the coming of Sir Henry Sidney to France. It seems clear that he was becoming an increasingly trusted agent of the queen mother in these years.